Performance of CaO for phenol steam reforming and water–gas shift reaction impacted by carbonation process. (19th October 2015) - Shuai, Chao; Hu, Song; He, Limo; Xiang, Jun; Su, Sheng; Sun, Lushi; Jiang, Long; Wang, Yi; Chen, Qindong; Liu, Changyi; Chi, Huanying
Abstract: CaO plays multiple roles in the in-situ gasification process of coal to produce hydrogen-rich gas. It is well known as a sorbent for CO2 capture, and as a catalyst to decompose tars and promote water–gas shift (WGS) reaction as well. It is very important to understand interactions between adsorption process and catalytic effect of CaO. In the current work, firstly, the carbonation degree of CaO and its reaction kinetics were studied at different CO2 partial pressures via thermogravimetric analyzer. Then the catalytic activity of calcium-based materials (CaO/CaCO3 ) at different carbonation degrees in the steam reforming of phenol (used as a model compound of tar) and WGS reaction were investigated, respectively. It showed that the catalytic activities of calcium-based materials for both reactions reduced with the increase of carbonation degree. On one hand, specified surface area had strong relationship with the catalytic activity of the materials for both reactions. On the other hand, the catalytic activity of calcium-based material in WGS reaction decreased due to CaCO3 formation. However, CaCO3 showed an obvious catalytic effect on phenol steam reforming. At last, performance of CaO for phenol steam reforming and WGS reaction were studied synchronously at different carbonation degrees. The results revealed that the phenol steam reforming and WGS reaction catalyzed by calcium-based materials were competitive with each other, and the presence of phenol strongly inhibited the conversion of CO in WGS reaction. Highlights: Effects of carbonation degrees on phenol steam reforming and WGS reaction were studied. Surface area strongly affects the catalytic activity of Ca-based materials on both reactions. CaCO3 shows clear activity on phenol steam reforming while not on WGS reaction. The catalytic phenol steam reforming and WGS reaction are competitive reactions.